Primary mucocele of the mastoid: An incidental finding. Issue 3 (30th January 2020) - Tonni, Daniela; Sessa, Michele; Redaelli de Zinis, Luca O.
Abstract: Mucocele is an accumulation of secretion products, desquamation, and inflammation within a body cavity: Localization in the mastoid is extremely rare. Erosion of bony walls and invasion of surrounding structures expose a patient to intra‐ and extracranial complications. Proper imaging work‐up and complete removal through mastoidectomy is warranted. Abstract : Mucocele is an accumulation of secretion products, desquamation, and inflammation within a body cavity: Localization in the mastoid is extremely rare. Erosion of bony walls and invasion of surrounding structures expose a patient to intra‐ and extracranial complications. Proper imaging work‐up and complete removal through mastoidectomy is warranted.